Fluctuación poblacional de la avispa de la agalla de los eucaliptos Leptocybe invasa F. en una plantación de Eucalyptus grandis en Montecarlo, Misiones = Population fluctuation of eucalyptus gall wasp Leptocybe invasa F. in a plantation of Eucalyptus grandis in Montecarlo Misiones - Mayntzhusen, Macarena; Eskiviski, Edgar Rafael; Schapovaloff, Maria Elena (Facultad de Ciencias Forestales, Universidad Nacional de Misiones, 2025)
The eucalyptus gall wasp, Leptocybe invasa, native from Australia, is a worldwide pest in Eucalyptus plantations. Several species of this genus are susceptible to L. invasa and within these is Eucalyptus. grandis, which is the main specie cultivated in Misiones. The aim of this study is to determine the population fluctuation of L. invasa in a plantation of E. grandis in Montecarlo Misiones. Five sticky chromatic traps were installed with periodic review every two weeks for two years. During the study period, two population peaks of the pest were determined during late summer and early spring.